Field exercises are useful for improving public health emergency responses - Eastwood, Keith; Durrheim, David; Merritt, Tony; Massey, Peter; Huppatz, Claire; Dalton, Craig; Hope, Kirsty; Moran, Lucille; Speare, Richard; Farrar, Kris (Western Pacific Surveillance and Response, 2013)
Problem: Emergencies resulting from disease outbreaks and extreme environmental events present significant challenges for health services. Context: Preparing to effectively manage emergencies is a core activity in public health units. Field exercises support consolidation of biopreparedness by testing plans, identifying weaknesses, providing training opportunities and developing surge capacity. Action: An extended field exercise to test response to a novel influenza strain was conducted in New South Wales, Australia in September 2008, eight months before the influenza A(H1N1) 2009 pandemic emerged. Lasting four days and involving over 300 participants, the exercise was set in the early response phase with the staggered presentation of 41 cases to 36 emergency departments in the health area. An additional 150 contacts were written into a complex scenario to test the public health response. Outcome: The subsequent pandemic emergence in mid-2009 offered a unique opportunity to assess the field exercise format for disaster preparedness. Most roles were adequately tested with recognized benefit during the actual pandemic response. However, the exercise did not adequately challenge the public health planning team that synthesizes surveillance data and forecasts risk, nor did it identify planning issues that became evident during the subsequent pandemic. Discussion: Field exercises offer the opportunity to rigorously test public health emergency preparedness but can be expensive and labour-intensive.